Wave In in auditory brainstem response suggests a high possibility of a high jugular bulb - Liu, Jia; Xie, Wanqin; Ding, Yan; Hu, Ya; Lai, Ruosha; Hu, Peng; Zhu, Ganghua (Frontiers in Pediatrics, 2023)
Background: Wave I n , referring to the negativity between waves I and II in auditory brainstem response (ABR), is an electrophysiological phenomenon observed in the earlier studies. The term 'high jugular bulb' describes a jugular bulb high-located in the posterior aspect of the internal acoustic canal (IAC). The present study aimed to explore the correlation between wave I n and the possibility of a high jugular bulb (HJB).The retrospective study included pediatric patients with profound hearing loss who were enrolled into the government-sponsored cochlear implantation program at an academic medical center between January 2019 and December 2022. The results of ABR test and high-resolution computed tomography (HRCT) of the temporal bone in the patients were analyzed. The position of jugular bulb was classified according to the Manjila and Semaan classification.Results: A total of 221 pediatric patients were included in the study. There were 24 patients, with a median age of 3 years and a range of 1 to 7 years, showing significant bilateral (n=21) or unilateral (n=3) wave I n (mean latency: right ear, 2.16 ms ± 0.22 ms; left ear, 2.20 ms ± 0.22 ms); and the other 197 patients showed an absence of ABR. HRCT images revealed that 18 of the 24 patients (75%) had HJB, comparing with 41 of the 197 patients with absent ABR (20.8%) having HJB. The ratio difference is statistically significant based on chi-square test (χ2 =32.10, p<0.01). Over 50% of the HJBs were classified to the type 4 jugular bulb, the position of which is above the inferior margin of the internal auditory canal.ABR Wave I n in child patients with profound hearing loss suggests a high possibility of HJB. The physiological mechanism underlying this correlation needs further investigation.